2002
DOI: 10.1177/1043986202018001006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Violence on Problem Behavior Among Adolescents

Abstract: This article measures the effects of exposure to violence on problem behavior (adjustment outcomes) among 306 African American middle and high school students in the state of Virginia. Relying on recent research examining the relationship between violent events and problem behavior, the study uses structural equation modeling to examine internalizing and externalizing behavioral characteristics (i.e., delinquency, depression, negative self-esteem, and avoidance) among African American youth exposed to violence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…Extensive evidence from youth unexposed to disasters supports a link between exposure to community violence and youth CPs (e.g., Margolin & Gordis, 2000, Lynch, 2003). Community violence exposure is associated with a variety of lasting CP-related outcomes, including violence and aggression, as well as substance abuse and involvement with the juvenile justice system (DuRant et al, 1994; Farrell & Bruce, 1997; Gorman-Smith & Tolan, 1998; McGee & Baker, 2002; Miller, Wasserman, Neugebauer, Gorman-Smith, & Kamboukos, 1999; Schwab-Stone et al, 1995; Vermeiren et al, 2003). Importantly, longitudinal work in community samples suggests that prior exposure to community violence has an effect on children’s aggressive behavior through both children’s imitation of violence and through the development of associated cognitions (Guerra et al, 2003).…”
mentioning
confidence: 99%
“…Extensive evidence from youth unexposed to disasters supports a link between exposure to community violence and youth CPs (e.g., Margolin & Gordis, 2000, Lynch, 2003). Community violence exposure is associated with a variety of lasting CP-related outcomes, including violence and aggression, as well as substance abuse and involvement with the juvenile justice system (DuRant et al, 1994; Farrell & Bruce, 1997; Gorman-Smith & Tolan, 1998; McGee & Baker, 2002; Miller, Wasserman, Neugebauer, Gorman-Smith, & Kamboukos, 1999; Schwab-Stone et al, 1995; Vermeiren et al, 2003). Importantly, longitudinal work in community samples suggests that prior exposure to community violence has an effect on children’s aggressive behavior through both children’s imitation of violence and through the development of associated cognitions (Guerra et al, 2003).…”
mentioning
confidence: 99%
“…Family background is also a significant predictor of violent behavior while controlling for traumatic victimization (Beta=.478). Therefore, these two predictors further increase the likelihood that the juvenile female will engage in violent behavior as seen in previous literature (McGee and Baker, 2002;McGee, 2003). Responses to the focus group and in-depth interview questions of this research revealed a series of patterns, themes and trends.…”
Section: Analysis and Findingsmentioning
confidence: 55%
“…Questions for the interviews and focus groups were developed from the literature based on previous research on patterns of violence among juveniles (McGee and Baker, 2002;McGee, 2003).…”
Section: Measurementmentioning
confidence: 99%
“…al., 2010) document continued high rates of victimization of children and youth, particularly among low-income, urban, minority youth. Consistently, two neighborhood measures-exposure to violence and neighborhood disadvantage-have been linked to increased youth victimization (Harding, 2009;Plybon & Kliewer, 2001) and juvenile offending (McGee & Baker, 2002;Zimmerman & Messner, 2010). Longitudinal studies of victimization suggest that prior exposure to community violence also predicts subsequent victimization (Lambert, Ialongo, Boyd, & Cooley, 2005;Menard, 2000).…”
Section: Neighborhood Correlates Of Victimization Of Children and Youthmentioning
confidence: 95%